Terrorism and the politics of fear - Altheide, David L. (Colección de libros electrónicos de ULoyola, 2006)
In this powerful new book, sociologist David L. Altheide demonstrates how the mass media constructs a politics of fear in America. He argues that politicians and decision-makers bear much of the blame for the promotion of fear among citizens, resulting in the loss of civil liberties in return for greater protection.